Revitalisasi Model Penanganan Anak Jalanan di Rumah Singgah - Suyatna, Hempri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2011)
The existence of a shelter actually has a strategic role for the handling of street children problems. Unfortunately, the shelter management is still conducted partially, therefore it is not effective in reducing the problem of street children. Thus, it is crucial to revitalize the model in handling street children problems. This paper offers approaches for improving the effectiveness of the shelter through the improvement in the aspects of input, process and termination. In addition, this paper also emphasizes the importance of reinforcing synergies among stakeholders in handling of street children problems.